The oral microbiome community variations associated with normal, potentially malignant disorders and malignant lesions of the oral cavity - Mok, S.F.; Chinna, Karuthan; Cheah, Y.K.; Ngeow, Wei Cheong; Zain, R.B.; Yap, S.F.; Ong, H.K.A. (College of Pathologists, Academy of Medicine Malaysia, 2017)
The human oral microbiome has been known to show strong association with various oral diseases including oral cancer. This study attempts to characterize the community variations between normal, oral potentially malignant disorders (OPMD) and cancer associated microbiota using 16S rDNA sequencing. Swab samples were collected from three groups (normal, OPMD and oral cancer) with nine subjects from each group. Bacteria genomic DNA was isolated in which full length 16S rDNA were amplified and used for cloned library sequencing. 16S rDNA sequences were processed and analysed with MOTHUR. A core oral microbiome was identified consisting of Firmicutes, Proteobacteria, Fusobacteria, Bacteroidetes and Actinobacteria at the phylum level while Streptococcus, Veillonella, Gemella, Granulicatella, Neisseria, Haemophilus, Selenomonas, Fusobacterium, Leptotrichia, Prevotella, Porphyromonas and Lachnoanae robaculum were detected at the genus level. Firmicutes and Streptococcus were the predominant phylum and genus respectively. Potential oral microbiome memberships unique to normal, OPMD and oral cancer oral cavities were also identified. Analysis of Molecular Variance (AMOVA) showed a significant difference between the normal and the cancer associated oral microbiota but not between the OPMD and the other two groups. However, 2D NMDS showed an overlapping of the OPMD associated oral microbiome between the normal and cancer groups. These findings indicated that oral microbes could be potential biomarkers to distinguish between normal, OPMD and cancer subjects.